Isoniazid-monoresistant tuberculosis in France: Risk factors, treatment outcomes and adverse events. (June 2021) - Bachir, Marwa; Guglielmetti, Lorenzo; Tunesi, Simone; Billard-Pomares, Typhaine; Chiesi, Sheila; Jaffré, Jérémy; Langris, Hugo; Pourcher, Valérie; Schramm, Frédéric; Lemaître, Nadine; Robert, Jérôme; ,; et al.
Highlights: No specific risk factors for isoniazid-monoresistant tuberculosis (HR-TB) identified. Routine implementation of line probe assays on clinical samples is warranted. In France HR-TB treatment outcomes are comparable to those for drug-susceptible TB. Abstract: Objectives: Isoniazid-monoresistant tuberculosis (HR-TB) is the most prevalent form of drug-resistant TB worldwide and in France and is associated with poorer treatment outcomes compared with drug-susceptible TB (DS-TB). The objective of this study was to determine the characteristics of HR-TB patients in France and to compare outcomes and safety of treatment for HR-TB and DS-TB. Methods: We performed a case-control multicenter study to identify risk factors associated with HR-TB and compare treatment outcomes and safety between HR-TB patients and DS-TB patients. Results: Characteristics of 99 HR-TB patients diagnosed and treated in the university hospitals of Paris, Lille, Caen and Strasbourg were compared with 99 DS-TB patients. Female sex (OR = 2.2; 1.0–4.7), birth in the West-Pacific World Health Organization region (OR = 4.6; 1.1–18.7) and resistance to streptomycin (OR = 77.5; 10.1–594.4) were found to be independently associated with HR-TB. Rates of treatment success did not differ significantly between HR-TB and DS-TB. Conclusions: Factors associated with HR-TB are not significant enough to efficiently screen TB patients at risk of HR-TB. The systematic implementation of rapid molecular testing on clinical samples remains the only effective way to make the early diagnosis of HR-TB and adapt treatment.